Write these laws on your children inside the world of conservative Christian homeschooling - Kunzman, Robert, 1968-; ebrary, Inc. (Boston, Mass. : Beacon Press, 2009)
Homeschooling is a large and growing phenomenon in American society--between 1999 and 2003 it grew at ten times the rate of public school enrollments. Current estimates suggest that about two million kids are homeschooled, but information about them is incomplete. Here, educator Robert Kunzman uses his unprecedented access to six conservative Christian homeschooling families to explore this elusive world, from the day-to-day lives of its adherents to its broader aspirations to transform American culture and politics. He shows us what their homeschooling experience looks like firsthand, what their political and religious beliefs are, and what their kids learn about democratic citizenship and engaging with people with different beliefs. Woven throughout Kunzman's narrative are larger questions about the purpose of public education, what makes an educated citizenry--and how American political and intellectual life could change as conservative Christian homeschooled children reach adulthood.--From publisher description.
Includes bibliographical references (p. 225-226) and index.
Electronic reproduction.
Keywords: Home schooling -- United States; Christian education -- United States; Electronic books